Post-publication peer review in biomedical journals: overcoming obstacles and disincentives to knowledge sharing (RT. A Journal on Research Policy and Evaluation, 2018)
The importance of post-publication peer review (PPPR) as a type of knowledge exchange has been emphasized by several authorities in research publishing, yet biomedical journals do not always facilitate this type of publication. Here we report our experience publishing a commentary intended to offer constructive feedback on a previously published article. We found that publishing our comment required more time and effort than foreseen, because of obstacles encountered at some journals. Using our professional experience as authors’ editors and our knowledge of publication policies as a starting point, we reflect on the probable reasons behind these obstacles, and suggest ways in which journals could make PPPR easier. In addition, we argue that PPPR should be more explicitly valued and rewarded in biomedical disciplines, and suggest how these publications could be included in research evaluations. Eliminating obstacles and disincentives to PPPR is essential in light of the key roles of post-publication analysis and commentary in drawing attention to shortcomings in published articles that were overlooked during pre-publication peer review.
Keywords: article processing charge; commentary; correspondence; editorial policies; instructions to authors; incentives; letter to the editor; open access; post-publication peer review; research evaluation criteria